Positive grid and negative grid alloy for industrial lead-acid storage battery and preparation method of positive grid and negative grid alloy
By using alloys of elements such as Pb, Ca, Sn, Al and Bi in industrial lead-acid batteries, combined with wet electrolysis and XRF technology, the problems caused by the difference in charging voltage of lead-acid batteries in different usage scenarios are solved, and the battery is improved Conductivity and corrosion resistance extend service life.
Patent Information
- Application Number
- CN202311518159.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-11-15
- Publication Date
- 2024-12-13
AI Technical Summary
In different usage scenarios, industrial lead-acid batteries have large hydrogen evolution amount, large electrolyte loss, unsaturated electricity, and reduced discharge capacity due to different charging voltages. The existing technology is difficult to meet the alloy requirements of different application scenarios.
Using positive and negative plate gate alloys including elements such as Pb, Ca, Sn, Al and Bi, 99.994% pure electrolytic lead is prepared by wet electrolysis process, and calcium-aluminum alloy and tin are added to the alloy configuration, using XRF technology Ensure element content standards and optimize the conductivity and corrosion resistance of the alloy.
It improves the low-voltage charging efficiency of industrial lead-acid batteries, extends the floating charging and circulation service life, improves the discharge capacity and mechanical strength, and adapts to the charging voltage requirements of different application scenarios.
Smart Images

Figure CN119120983A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of industrial lead-acid battery plate manufacturing, and in particular relates to a positive grid, a negative grid alloy and a configuration method for an industrial lead-acid battery. Background Art
[0002] Lead-acid batteries have a history of more than 100 years. Due to the advantages of raw material lead, such as rich mineral resources, low price and high battery recycling rate, the lead-acid battery products produced are cost-effective, safe and have a wide range of applications. They are widely used in various fields such as transportation power energy and communications, electricity, UPS uninterruptible power supply and energy storage base stations, especially in large data center computer rooms with high safety requirements. Industrial lead-acid batteries are the best choice.
[0003] The main components of lead-acid batteries are positive plates, negative plates, separators, battery shell covers, electrolytes, positive and negative terminals and safety valves. Positive and negative plates are the heart of the battery and are the carriers for converting chemical energy into electrical energy. The quality of the plates directly affects the discharge performance and service life of the battery.
[0004] The main components of the positive plate are the positive grid and positive lead paste, and the main components of the negative plate are the negative grid and negative lead paste. The grid is the skeleton of the plate, the carrier of the lead paste, and the conductive path framework. Good conductivity directly affects the discharge performance and charge and discharge service life of the battery. The content of various metal elements in the positive and negative grid alloys directly affects the conductivity and corrosion resistance of the grid.
[0005] In terms of cost and battery performance requirements, lead-acid batteries with different usage ranges have different alloy requirements to adapt to different application scenarios. Lead-acid batteries in different application scenarios have significantly different requirements for charging voltage. A high charging voltage will result in a large amount of hydrogen evolution in the battery, a large loss of electrolyte, and a shortened lifespan; a low charging voltage will result in an inadequate charge of the battery, a reduced discharge capacity, and a faster capacity decay.
[0006] Industrial lead-acid batteries are often used for backup power supplies. The floating charge voltage of UPS equipment commonly used internationally is generally 2.20-2.25V / cell, and the equalization charge voltage is generally 2.30-2.35V / cell. The charging voltage is relatively fixed and cannot be adjusted at will. Industrial lead-acid batteries must adapt to the above charging voltage. If lead-acid batteries are to adapt to the above voltages, in addition to using appropriate electrolyte density and lead paste formula, the content of each constituent element in the positive and negative grid alloys used for the positive and negative plates is even more critical. Therefore, we need to provide a positive grid, negative grid alloy and configuration method for industrial lead-acid batteries. Summary of the invention
[0007] The purpose of the present invention is to provide a positive grid, negative grid alloy and configuration method for industrial lead-acid batteries, solve the conductivity and corrosion resistance of industrial lead-acid battery plate grids, improve the low-voltage charging efficiency of industrial lead-acid batteries, improve the discharge capacity, and increase the floating charge use and cycle life, so as to solve the problem that lead-acid batteries with different use ranges in the prior art have different alloy requirements in the above background technology to adapt to different application scenarios. Lead-acid batteries in different application scenarios have significantly different requirements for charging voltage. If the charging voltage is high, the battery will have a large amount of hydrogen evolution, large electrolyte loss, and shortened life; if the charging voltage is low, the battery will not be fully charged, the battery discharge capacity will be reduced, and the capacity decay will be fast.
[0008] To achieve the above object, the present invention adopts the following technical solution: A positive grid and negative grid alloy for industrial lead-acid batteries, including main raw materials Pb, Ca, Sn, Al and main impurity Bi content and other impurities content weight percentage composition:
[0009]
[0010]
[0011] A method for configuring positive grid and negative grid alloys for industrial lead-acid batteries comprises the following steps:
[0012] Step 1: Preparation of electrolytic lead: crude lead is subjected to a wet electrolytic process to remove impurities and then smelted to produce pure electrolytic lead with a Pb content of ≥ 99.994%;
[0013] Step 2: Add the electrolytic lead, calcium aluminum alloy, tin ingot and other materials in step 1 in proportion to the alloy configuration lead pot;
[0014] Step 3: After fully melting and stirring, take samples for condensation and mill the surface, then use a spectrometer to test the content of each element to meet the alloy content standards for positive and negative grids.
[0015] Preferably, in step 1, the crude lead produced by the raw material bottom blowing furnace and the reduction furnace and the purchased crude lead are firstly refined in a lead melting pot, after removing impurities such as copper and tin, and adjusting the antimony content, and then cast into lead anode plates, and then subjected to wet electrolysis. When the lead anode plates are electrolyzed, the lead anode plates are used as anodes, the starting electrode sheets made of electrolytic lead are used as cathodes, and the lead fluoride silicate solution is used as the electrolyte, and the cathode lead containing more than 99.994% of lead is electrolyzed in the electrolytic cell. The cathode lead is melted, impurities are removed, and ingots are cast in the lead electrolytic pot to obtain the product lead ingots.
[0016] Preferably, in step 2, tin is added to improve the chemical properties of the interface between the grid and the active material, prevent the formation of a passivation film, and increase the bonding force between the grid and the active material. It can also reduce the oxidation loss of the lead-antimony molten liquid when it is stationary, slow down the solidification rate of the lead alloy, and improve the flowability during casting. At the same time, tin can improve the corrosion resistance of the alloy and the conductivity of the anode corrosion film, and improve the cycle life of the battery.
[0017] Preferably, 1.20-1.30% Sn is added to the positive grid, and 0.20-0.30% Sn is added to the negative grid, which significantly improves the mechanical strength and creep resistance of the alloy, and is beneficial to deep cycle charging and discharging of maintenance-free batteries.
[0018] Preferably, the Al-containing alloy is considered to be the most commonly used and relatively stable alloy for small sealed lead-acid battery grid alloys. Its main advantage is that adding an appropriate amount of Al to the alloy melt can significantly reduce the burn-off amount of Ca. Experiments on the stability of the Ca content using different protection measures during melting show that when the Ca content drops from 0.15% to 0.05%, adding 0.05% Al can stabilize the alloy for about 168 hours. When charcoal or AlO is used as a covering layer for protection, the Ca content in the alloy drops to below 0.05% within 1.5 to 2 hours.
[0019] Preferably, the Bi has a greater influence on the electrical and thermal conductivity of the Pb-Ca alloy, and is brittle and easily crushed. The Bi content in the grid alloy needs to be strictly controlled to be ≤0.0025% to ensure the corrosion resistance and hardness of the grid alloy.
[0020] Preferably, the small amount of Ag is applied to stationary or underwater submarine batteries, which are characterized in that the batteries have low outgassing during charging and discharging.
[0021] Preferably, in step 3, XRF (X-ray fluorescence) is used, which is a non-destructive analytical technique for determining the elemental composition of a material. XRF technology determines the chemical properties of a sample by analyzing the fluorescent (or secondary) X-rays scattered by the sample when excited by a primary X-ray source. Each element in the sample will produce a specific and unique set of fluorescent X-rays ("fingerprints") after being excited.
[0022] Preferably, as a non-destructive elemental analysis method, the XRF can directly analyze metal samples, with a concentration range of ppm to 100%, and the content information of all components can be obtained in one injection. The determination of 74 elements (O to Am), such as Mn, Cr, Ni, Mo, V, Cu, Fe, etc., can be completed within 5 minutes.
[0023] Technical effects and advantages of the present invention: The positive grid and negative grid alloy and configuration method for industrial lead-acid batteries proposed in the present invention have the following advantages over the prior art:
[0024] The present invention prepares electrolytic lead by: removing impurities from crude lead through a wet electrolysis process and then smelting to produce pure electrolytic lead with a Pb content of ≥99.994%; adding the electrolytic lead in step 1 and materials such as calcium aluminum alloy and tin ingots in proportion into an alloy configuration lead pot; fully melting and stirring, sampling, condensing, milling the surface, and testing the content of each element with a spectrometer to meet the alloy content standard for positive and negative grids, thereby solving the problems of conductivity and corrosion resistance of industrial lead-acid battery pole plate grids, improving the low-voltage charging efficiency of industrial lead-acid batteries, improving the discharge capacity, and increasing the floating charge use and cycle service life.
[0025] Other features and advantages of the present invention will be described in the following description, and partly become obvious from the description, or be understood by implementing the present invention. The purpose and other advantages of the present invention can be realized and obtained by the structures pointed out in the description and the drawings. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 is a flow chart of the steps of the present invention;
[0027] Figure 2 Schematic diagram of raw materials and impurity elements of the present invention. DETAILED DESCRIPTION
[0028] The following will be combined with the accompanying drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments. The specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0029] The present invention provides Figure 1-2 The positive grid and negative grid alloy for industrial lead-acid batteries shown in the figure includes the main raw materials Pb, Ca, Sn, Al and the main impurity Bi content and other impurities content weight percentage composition:
[0030]
[0031]
[0032] A method for configuring positive grid and negative grid alloys for industrial lead-acid batteries comprises the following steps:
[0033] Step 1: Preparation of electrolytic lead: crude lead is subjected to a wet electrolytic process to remove impurities and then smelted to produce pure electrolytic lead with a Pb content of ≥ 99.994%;
[0034] Step 2: Add the electrolytic lead, calcium aluminum alloy, tin ingot and other materials in step 1 in proportion to the alloy configuration lead pot;
[0035] Step 3: After fully melting and stirring, take samples for condensation and mill the surface, then use a spectrometer to test the content of each element to meet the alloy content standards for positive and negative grids.
[0036] In step 1, the crude lead produced by the raw material bottom blowing furnace and the reduction furnace and the purchased crude lead are firstly refined in the lead melting pot, after removing impurities such as copper and tin, and adjusting the antimony content, and then cast into lead anode plates, and then carry out wet electrolysis. When the lead anode plate is electrolyzed, the lead anode plate is used as the anode, the starting electrode sheet made of electrolytic lead is used as the cathode, and the lead fluoride silicate solution is used as the electrolyte. The cathode lead containing more than 99.994% of lead is electrolyzed in the electrolytic cell. The cathode lead is melted in the lead electrolytic pot, oxidized and impurities are removed, and ingots are cast to obtain the product lead ingots.
[0037] In step 2, tin is added to improve the chemical properties of the interface between the grid and the active material, prevent the formation of a passivation film, and increase the bonding force between the grid and the active material. It can also reduce the oxidation loss of the lead-antimony molten liquid when it is stationary, slow down the solidification rate of the lead alloy, and improve the flowability during casting. At the same time, tin can improve the corrosion resistance of the alloy and the conductivity of the anode corrosion film, thereby improving the cycle life of the battery.
[0038] Adding 1.20-1.30% Sn into the positive grid and 0.20-0.30% Sn into the negative grid can significantly improve the mechanical strength and creep resistance of the alloy, which is beneficial to the deep cycle charging and discharging of maintenance-free batteries.
[0039] Alloys containing Al are considered to be the most commonly used and relatively stable alloys for small sealed lead-acid battery grids. Their main advantage is that adding an appropriate amount of Al to the alloy melt can significantly reduce the amount of Ca burned. Experiments on the stability of Ca content using different protection measures during melting show that when the CA content drops from 0.15% to 0.05%, adding 0.05% Al, the stability period of the alloy is about 168 hours. When charcoal or AlO is used for covering protection, the Ca content in the alloy drops to below 0.05% within 1.5 to 2 hours.
[0040] Bi has a great influence on the electrical and thermal conductivity of Pb-Ca alloy, and is brittle and easily crushed. The Bi content in the grid alloy needs to be strictly controlled to ≤0.0025% to ensure the corrosion resistance and hardness of the grid alloy.
[0041] A small amount of Ag is used in stationary or underwater submarine batteries, which are characterized by low outgassing during charging and discharging.
[0042] In step 3, XRF (X-ray fluorescence) is used, which is a non-destructive analytical technique for determining the elemental composition of materials. XRF technology determines the chemical properties of a sample by analyzing the fluorescent (or secondary) X-rays scattered by the sample when it is excited by a primary X-ray source. Each element in the sample will produce a specific and unique set of fluorescent X-rays ("fingerprint") when excited.
[0043] As a non-destructive elemental analysis method, XRF can directly analyze metal samples, with a concentration range of ppm to 100%, and the content information of all components can be obtained with one injection. The determination of 74 elements (O to Am) such as Mn, Cr, Ni, Mo, V, Cu, Fe, etc. can be completed within 5 minutes.
[0044] Working principle: Preparation of electrolytic lead: crude lead is subjected to wet electrolysis process to remove impurities and then smelted to produce pure electrolytic lead with a Pb content of ≥99.994%; the electrolytic lead and calcium aluminum alloy, tin ingots and other materials in step 1 are added proportionally to the alloy configuration lead pot; after sufficient melting and stirring, samples are taken for condensation and the surface is milled and tested with a spectrometer to ensure that the content of each element reaches the alloy content standard for positive and negative grids.
[0045] Finally, it should be noted that the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, it is still possible for those skilled in the art to modify the technical solutions described in the aforementioned embodiments or to make equivalent substitutions for some of the technical features therein. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A positive grid and negative grid alloy for industrial lead-acid batteries, Features: The weight percentage of the main raw materials Pb, Ca, Sn, Al and the main impurity Bi and other impurities is as follows:
2. A method for configuring positive grid and negative grid alloys for industrial lead-acid batteries, Features: The following steps are involved: Step 1: Preparation of electrolytic lead: crude lead is subjected to a wet electrolytic process to remove impurities and then smelted to produce pure electrolytic lead with a Pb content of ≥ 99.994%; Step 2: Add the electrolytic lead, calcium aluminum alloy, tin ingot and other materials in step 1 in proportion to the alloy configuration lead pot; Step 3: After fully melting and stirring, take samples for condensation and mill the surface, then use a spectrometer to test the content of each element to meet the alloy content standards for positive and negative grids.
3. A method for configuring positive grid and negative grid alloys for industrial lead-acid batteries according to claim 1, Features: In step 1, the crude lead produced by the raw material bottom blowing furnace and the reduction furnace and the purchased crude lead are firstly refined in the lead melting pot, after removing impurities such as copper and tin, and adjusting the antimony content, and then cast into lead anode plates, and then subjected to wet electrolysis. When the lead anode plates are electrolyzed, the lead anode plates are used as anodes, the starting electrode sheets made of electrolytic lead are used as cathodes, and the lead fluoride silicate solution is used as the electrolyte, and the cathode lead containing more than 99.994% of lead is electrolyzed in the electrolytic cell. The cathode lead is melted, impurities are removed, and ingots are cast in the lead electrolytic pot to obtain the product lead ingots.
4. A positive grid, a negative grid alloy and a configuration method for an industrial lead-acid battery according to claim 1, Features: In step 2, tin is added to improve the chemical properties of the interface between the grid and the active material, prevent the formation of a passivation film, and increase the bonding force between the grid and the active material. It can also reduce the oxidation loss of the lead melt when standing, slow down the solidification rate of the lead alloy, and improve the flowability during casting. At the same time, tin can improve the corrosion resistance of the alloy and the conductivity of the anode corrosion film, thereby improving the cycle life of the battery.
5. A positive grid, a negative grid alloy and a configuration method for an industrial lead-acid battery according to claim 3, Features: The positive grid contains 1.20-1.30% Sn, and the negative grid contains 0.20-0.30% Sn, which significantly improves the mechanical strength and creep resistance of the alloy and is beneficial to the deep cycle charge and discharge of the maintenance-free battery.
6. A positive grid, a negative grid alloy and a configuration method for an industrial lead-acid battery according to claim 1, Features: The Al-containing alloy is considered to be the most commonly used and relatively stable alloy for small sealed lead-acid battery grids. Its main advantage is that adding an appropriate amount of Al to the alloy melt can significantly reduce the burn-off amount of Ca. Experiments on the stability of the Ca content using different protection measures during melting show that when the CA content drops from 0.15% to 0.05%, the addition of 0.05% Al can stabilize the alloy for about 168 hours. When charcoal or AlO is used as a covering layer for protection, the Ca content in the alloy drops to below 0.05% within 1.5 to 2 hours.
7. A positive grid, a negative grid alloy and a configuration method for an industrial lead-acid battery according to claim 1, Features: The Bi has a great influence on the electrical and thermal conductivity of the Pb-Ca alloy, has a molecular weight greater than that of lead, is brittle and easily crushed, and the Bi content in the grid alloy needs to be strictly controlled to ≤0.0025% to ensure the corrosion resistance and hardness of the grid alloy.
8. A positive grid, a negative grid alloy and a configuration method for an industrial lead-acid battery according to claim 1, Features: The small amount of Ag is applied to stationary batteries or underwater submarine batteries, which are characterized by low outgassing during charging and discharging of the batteries.
9. A positive grid, a negative grid alloy and a configuration method for an industrial lead-acid battery according to claim 1, Features: In step 3, XRF (X-ray fluorescence) is a non-destructive analytical technique used to determine the elemental composition of materials. XRF technology determines the chemical properties of a sample by analyzing the fluorescent (or secondary) X-rays scattered by the sample when excited by a primary X-ray source. Each element in the sample will produce a specific and unique set of fluorescent X-rays ("fingerprints") after being excited.
10. A positive grid, a negative grid alloy and a configuration method for an industrial lead-acid battery according to claim 9, Features: As a non-destructive elemental analysis method, XRF can directly analyze metal samples, with a concentration range of ppm to 100%, and the content information of all components can be obtained in one injection. The determination of 74 elements (O to Am), such as Mn, Cr, Ni, Mo, V, Cu, Fe, etc., can be completed within 5 minutes.
